Evidence for lateral gene transfer (LGT) in the evolution of eubacteria-derived small GTPases in plant organelles - Suwastika, I. Nengah; Denawa, Masatsugu; Yomogihara, Saki; Im, Chak Han; Bang, Woo Young; Ohniwa, Ryosuke L.; Bahk, Jeong Dong; Takeyasu, Kunio; Shiina, Takashi (Frontiers in Plant Science, 2014)
The genomes of free-living bacteria frequently exchange genes via lateral gene transfer (LGT), which has played a major role in bacterial evolution. LGT also played a significant role in the acquisition of genes from non-cyanobacterial bacteria to the lineage of ‘primary’ algae and land plants. Small GTPases are widely distributed among prokaryotes and eukaryotes. In this study, we inferred the evolutionary history of organelle-targeted small GTPases in plants. Arabidopsis thaliana contains at least one ortholog in seven subfamilies of OBG-HflX-like and TrmE-Era-EngA-YihA-Septin-like GTPase superfamilies (together referred to as Era-like GTPases). Subcellular localization analysis of all Era-like GTPases in Arabidopsis revealed that all thirteen eubacteria-related GTPases are localized to chloroplasts and/or mitochondria, whereas archaea-related DRG and NOG1 are localized to the cytoplasm and nucleus, respectively, suggesting that chloroplast- and mitochondrion-localized GTPases are derived from the ancestral cyanobacterium and α-proteobacterium, respectively, through endosymbiotic gene transfer (EGT). However, phylogenetic analyses revealed that plant organelle GTPase evolution is rather complex. Among the eubacterium-related GTPases, only four localized to chloroplasts (including one dual targeting GTPase) and two localized to mitochondria were derived from cyanobacteria and α-proteobacteria, respectively. Three other chloroplast-targeted GTPases were related to α-proteobacterial proteins, rather than to cyanobacterial GTPases. Furthermore, we found that four other GTPases showed neither cyanobacterial nor α-proteobacterial affiliation. Instead, these GTPases were closely related to clades from other eubacteria, such as Bacteroides (Era1, EngB-1, and EngB-2) and green non-sulfur bacteria (HflX). This study thus provides novel evidence that LGT significantly contributed to the evolution of organelle-targeted Era-like GTPases in plants.